Sport and Social Inclusion: Evidence-Based Policy and Practice - Coalter, Fred (Social Inclusion, 2017)
This commentary reflects on my experience of compiling the Value of Sport Monitor —an on-line resource of policy-relevant, research on the social impacts of sport—for eight years. The commentary critically evaluates the assumption of the Value of Sport Monitor that social science research in sport is cumulative and it explores sports interest groups’ varying attitudes to the nature of evidence. It illustrates that widespread conceptual and methodological inconsistencies and weaknesses in research greatly reduce the ability to identify best practice and ‘best buys’ as a basis for policy. The commentary concludes by proposing that a way forward for research to contribute to policy and practice is via theory-based evaluation.